DEVELOPMENT STAGES OF INFORMATION COMMUNICATION TOOLS - Olimova Mehrizar Akmalovna (Journal of new century innovations, 2023)
Abstract: Today, various types of information communication businesses have emerged, which are engaged in the collection, processing, transmission and preparation of these resources based on the personal requirements of consumers, and they are the basis of this market. One of the main features of the 1990s is the emergence of various and new participants in the information and communication business. Among them, one can list database developers, various interactive services, information brokers. The formation of market relations between the participants of the information and communication business, the development of unique methods of competition, and the emergence of potential consumers - all this is international and indicates the formation of national interactive services. Figure 1 below shows the diagram of the organizational and functional relations of the participants of this market. It can be seen that the segments, objects and subjects and participants of the information and communication market form a whole system. It should be noted that the role of the state in the formation and development of the information and communication market in our republic is significant. The analysis of the achievements of the world information and communication technologies made it possible to develop a functional model of the information and communication business. defined by three main factors: environment, market and tasks. A set of these factors helps to conduct a unified financial and economic policy on the formation of interactive services.